Collective narcissism and the growth of conspiracy thinking over the course of the 2016 United States presidential election: a longitudinal analysis - De Zavala, A. G. (2018)
Using data from a longitudinal study of American adults collected between July and November 2016, we examine the hypothesis that American collective narcissism (CN) would uniquely predict increases in conspiracy thinking during the 2016 presidential campaign. Going beyond previous findings, our results indicate that CN (but not in-group identification) predicted growth in general conspiracy thinking—that is, a tendency to view political events in terms of group-based conspiracies—over the course of the 2016 US presidential campaign. This relationship is found even after accounting for other predictors such as demographics, political knowledge, social trust, authoritarianism, and need for cognitive closure.